The Effect of Paclobutrazol Concentration on the Growth and Production of Several Varieties of Mung Beans (Vigna radiata L.) - Aisyah Br Sembiring; Ariani Syahfitri Harahap; Suryani Sajar (Sean Institute, 2026)
This study aims to determine the effect of paclobutrazol concentration on the growth and production of several varieties of mung bean (Vigna radiata L). This study used a factorial Randomized Block Design (RBD) with paclobutrazol concentration treatments (0, 10, 20, and 30 ppm) and mung bean varieties (Vima 2, Kutilang, and Vimil 1). The parameters observed in this study were plant height, flowering age, number of productive branches, number of pods per sample, number of pods per plot, seed weight per sample, seed weight per plot, weight of 100 seeds per plot, and root length. The results showed that the administration of paclobutrazol concentration significantly affected the parameters of plant height 2, and 5 WAP, flowering age, number of productive branches, number of pods per sample, number of pods per plot, seed weight per sample, seed weight per plot, and root length, and did not significantly affect the parameters of plant height 3, 4 WAP and weight of 100 seeds per plot, and the variety treatment showed a significant effect on the parameters of plant height 2, 3, 5 WAP, number of productive branches, number of pods per sample, number of pods per plot, seed weight per sample, seed weight per plot, weight of 100 seeds per plot, and root length and did not significantly affect the parameters of plant height 4 WAP flowering age. and the interaction between the two concentrations had no significant effect. The concentration of paclobutrazol at 20 ppm and the Kutilang variety showed a significant effect on the growth and production of mung bean plants.